Experimental study of the potential hazards of surgical smoke from powered instruments. Issue 12 (2nd September 2015) - In, S. M.; Park, D.‐Y.; Sohn, I. K.; Kim, C.‐H.; Lim, H. L.; Hong, S.‐A.; Jung, D. Y.; Jeong, S.‐Y.; Han, J. H.; Kim, H. J.
<x xml:space="preserve">Abstract</x> Background Many surgical instruments have been replaced with powered devices in open gastrointestinal and laparoscopic surgery. The production of smoke as a result of vaporization of surgical tissue is inevitable, and exposure to surgical smoke is a long‐standing concern. These vapours are potentially hazardous to patients and surgical teams. The present research was designed to compare various surgical devices to determine whether viable cells exist in their surgical smoke. Methods The search for viable cells in surgical smoke was conducted using both in vitro and in vivo experiments. Various cancers were cauterized with electrocautery, radiofrequency ablation and ultrasonic scalpels, and the resulting surgical smoke was aspirated with Transwell® membrane; viable cells were sought in the surgical smoke. In an in vivo experiment, samples of SCC7 were cauterized with an ultrasonic scalpel and the sediment from the rinsed Transwell® membrane liquid after centrifugation was injected subcutaneously into the lower back of mice. Results Viable cells were found only in the smoke from ultrasonic scalpels (in all 25 samples taken 5 cm from the cautery; 2 of 25 samples at 10 cm). Viable cells in the surgical smoke from ultrasonic scalpels implanted in mice grew in 16 of 40 injection sites. Histological and biochemical analyses revealed that these cancer cells were identical to the cancer cells cauterized by the ultrasonic scalpel. Conclusion Viable tumour cells are produced in the surgical smoke from tumour dissection by ultrasonic scalpel. <boxed-text content-type="box" id="bjs9910-blkfxd-0001" position="anchor" orientation="portrait"> Surgical relevance Surgical smoke is a byproduct of dissection using a number of powered devices. Hazards to operating room personnel and patients are unclear. This study has shown that use of an ultrasonic dissection device can produce smoke that contains viable tumour cells. Although the model is somewhat artificial, a theoretical risk exists, and measures to evacuate surgical smoke efficiently are important. </boxed-text>